A Manganese Alternative to Gadolinium for MRI Contrast - Gale, Eric M; Atanasova, Iliyana P; Blasi, Francesco; Ay, Ilknur; Caravan, Peter (Journal of the American Chemical Society, 2015)
Contrast-enhanced computed tomography (CT) and magnetic resonance imaging (MRI) are routinely used to diagnose soft tissue and vascular abnormalities. However, safety concerns limit the use of iodinated and gadolinium (Gd)-based CT and MRI contrast media in renally compromised patients. With an estimated 14% of the US population suffering from chronic kidney disease (CKD), contrast media compatible with renal impairment is sorely needed. We present the new manganese(II) complex [Mn(PyC3A)(H2O)]− as a Gd alternative. [Mn(PyC3A)(H2O)]− is among the most stable Mn(II) complexes at pH 7.4 (log K ML = 11.40). In the presence of 25 mol equiv of Zn at pH 6.0, 37 °C, [Mn(PyC3A)(H2O)]− is 20-fold more resistant to dissociation than [Gd(DTPA)(H2O)]2–. Relaxivity of [Mn(PyC3A)(H2O)]− in blood plasma is comparable to commercial Gd contrast agents. Biodistribution analysis confirms that [Mn(PyC3A)(H2O)]− clears via a mixed renal/hepatobiliary pathway with >99% elimination by 24 h. [Mn(PyC3A)(H2O)]− was modified to form a bifunctional chelator and 4 chelates were conjugated to a fibrin-specific peptide to give Mn-FBP. Mn-FBP binds the soluble fibrin fragment DD(E) with K d = 110 nM. Per Mn relaxivity of Mn-FBP is 4-fold greater than [Mn(PyC3A)(H2O)]− and increases 60% in the presence of fibrin, consistent with binding. Mn-FBP provided equivalent thrombus enhancement to the state of the art Gd analogue, EP-2104R, in a rat model of arterial thrombosis. Mn metabolite analysis reveals no evidence of dechelation and the probe was >99% eliminated after 24 h. [Mn(PyC3A)(H2O)]− is a lead development candidate for an imaging probe that is compatible with renally compromised patients.